2004
DOI: 10.1051/0004-6361:20034614
|View full text |Cite
|
Sign up to set email alerts
|

An improved ephemeris and physical elements of ER Vul

Abstract: Abstract. New photoelectric UBV and BVRI observations, secured during August−November of 2002 at two observatories distant in local time are analyzed together with two earlier photometric data sets and all available radial velocities to derive the most accurate ephemeris of the binary and to set limits on its basic physical elements. These observations were obtained as a support for a high-dispersion spectroscopic study, results of which will be published separately. It was found that radial velocities and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 11 publications
0
15
1
1
Order By: Relevance
“…Harmanec et al (2004) b. Pop & Vamoş (2013) c. Gray et al (2001) d. Nordström et al (2004) demonstrated that the Doppler imaging code can be used for determining stellar parameters for both single and binary stars, and can avoid systematic errors caused by the effects of starspot distortions (Barnes et al 1998(Barnes et al , 2004.…”
Section: System Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…Harmanec et al (2004) b. Pop & Vamoş (2013) c. Gray et al (2001) d. Nordström et al (2004) demonstrated that the Doppler imaging code can be used for determining stellar parameters for both single and binary stars, and can avoid systematic errors caused by the effects of starspot distortions (Barnes et al 1998(Barnes et al , 2004.…”
Section: System Parametersmentioning
confidence: 99%
“…Fortunately, ER Vul has been extensively studied, and the physical and orbital parameters have been derived by many authors. We adopted the improved values of the radial velocity amplitude of the primary star (K1), mass ratio (q) and inclination (i) derived from both the photometric data and the radial velocities (Harmanec et al 2004). The first conjunction time (T0) and the orbital period (P) were from the paper by Pop & Vamoş (2013).…”
Section: System Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Applications on one side include Mayer et al (1991) [HJD 0 , P 0 , and dω/dt from RV 's and light curves of the EB V1765 Cygni]; Harmanec & Scholz (1993) [HJD 0 , P , and dP/dt from a century of RV 's for β Lyrae †]; Tarasov et al (1995) [HJD 0 and P from RV 's of the non-eclipsing triple system Persei]; Harmanec et al (2004) [P and dP/dt for ER Vulpeculae, a solar-type EB ]; Janik et al (2003) [dω/dt for the welldetached EB V436 Persei]; and Horn et al (1996) [HJD 0 ,dP/dt,dω/dt,HJD 0,3b ,and P 3b from RV 's of the non-eclipsing triple system 55 Ursae Majoris]. The Horn et al third body results for 55 UMa agree accurately with speckle (i.e.…”
Section: Whole Light and Velocity Curve Ephemerides And Extension To mentioning
confidence: 99%